(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud Computing is an emerging as well as the next generation technology. It provides different services such as SaaS, PaaS, IaaS. It is an Internet based technology where quality services are provided to users including data and software, on remote servers. In order to achieve secure cloud, there exists certain techniques such as erasure-coded data, authentication, message-digest algorithms. There are a number of algorithms and their methodologies available for achieving data security. In this paper we look at the current researchers related to data security issues like confidentiality and authentication. In particular, we will discuss how to secure data on certain servers.